Health insurance type, healthcare utilization and out-of-pocket expenditure in the face of COVID-19: Evidence from Thai national survey data - Chantal Herberholz; Piraya Saichol; Kannika Damrongplasit (PLoS ONE, 2025)
Objectives Universal population coverage for healthcare was achieved in several countries, including Thailand, while retaining fragmented health insurance schemes. Fragmentation in health financing has been debated since it can exacerbate inequalities, especially when health systems are under stress due to a public health emergency. This study examines whether the type of public health insurance affects outpatient healthcare utilization and out-of-pocket expenditure in Thailand before and during the coronavirus pandemic. Methods Using the 2019 and 2021 waves of the nationally representative Health and Welfare Survey and a repeated cross-sectional design, logit and multinomial logit models are estimated to investigate the effect of health insurance type on outpatient healthcare utilization (n=10,220), while two-part and Tobit models are employed as alternative models for the analysis of out-of-pocket expenditure (n=12,014). For both healthcare utilization and out-of-pocket expenditure, the study also explores models with and without interactive terms between insurance coverage type and a dummy variable capturing the COVID-19 period. Results Type of health insurance is found to impact provider choice (i.e., designated versus non-designated providers) rather than outpatient care utilization per se. Insignificant interaction effects indicate further that the relationship between health insurance type and outpatient care utilization is not affected by the pandemic. The regression results also show that health insurance type is associated with out-of-pocket expenditure (separated into medical and transportation spending) but the magnitude of the effect is relatively small, pre- and peri-pandemic. High-need persons with, for example, chronic conditions, however, face a higher out-of-pocket burden in terms of medical and transportation spending. Conclusion Overall, the results suggest that Thailand’s universal health coverage system has continued to live up to its promise of access and financial protection in the face of COVID-19, despite existing fragmentation. Notwithstanding, this study highlights that universal health coverage is an ongoing effort that requires careful monitoring, inter alia to mitigate undesirable consequences of fragmentation and to ensure that high-need and other vulnerable persons are not left behind.